Kampung Budaya: Upaya PT Pertamina EP Jambi Field dalam Meningkatkan Pendidikan Suku Anak Dalam - Afrianto, Afrianto; Arifin, M. Zainul; Hidayah, Lutfia Nur; Safrida, Safrida (Indonesian Journal Publisher, 2024)
Suku Anak Dalam (SAD), a part of the Remote Indigenous Communities (KAT), faces significant social challenges, particularly in access to education. To address this, PT Pertamina EP Jambi Field has initiated the